1959
DOI: 10.1111/j.1476-5381.1959.tb00961.x
|View full text |Cite
|
Sign up to set email alerts
|

The Actions of Bretylium: Adrenergic Neurone Blocking and Other Effects

Abstract: Bretylium caused a specific and lasting depression of many excitatory and inhibitory responses evoked by electrical stimulation of the peripheral sympathetic nervous system, probably by impairing conduction of impulses in adrenergic neurones with consequent failure of noradrenaline and adrenaline release. This effect, which will be referred to as the adrenergic neurone blocking action, was preceded by weak sympathomimetic effects. In the presence of bretylium the effects of adrenaline and noradrenaline were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
92
0

Year Published

1962
1962
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(103 citation statements)
references
References 18 publications
(12 reference statements)
11
92
0
Order By: Relevance
“…It has been reported that betylium inhibits the atrial responses to the sympathetic as well as vagal stimulation (25). On the other hand, no effect of bretylium on the parasympa thetic nervous system and on the responses of the rabbit's intestine to acetylcholine has been reported elsewhere (27). The depressant effect of bretylium on the negative responses of the atria to cholinergic stimulation may partly be due to the blocking effect of bretylium on the endogenous noradrenaline, supposedly regulating the choli nergic transmission mechanism in the isolated heart, and partly to the decrease in sensitivity of the atria to endogenously released acetylcholine.…”
Section: Discussionmentioning
confidence: 94%
“…It has been reported that betylium inhibits the atrial responses to the sympathetic as well as vagal stimulation (25). On the other hand, no effect of bretylium on the parasympa thetic nervous system and on the responses of the rabbit's intestine to acetylcholine has been reported elsewhere (27). The depressant effect of bretylium on the negative responses of the atria to cholinergic stimulation may partly be due to the blocking effect of bretylium on the endogenous noradrenaline, supposedly regulating the choli nergic transmission mechanism in the isolated heart, and partly to the decrease in sensitivity of the atria to endogenously released acetylcholine.…”
Section: Discussionmentioning
confidence: 94%
“…It may be considered that as well as nicotine, the effect of tyramine on amylase secretion is mediated through catecholamine in adrenergic receptor level. The stimulating effect of bretylium on amylase secretion, similar to its sympa thomimetic effects in various organs, may be sympathomimetic one, which is mainly at tributable to a peripheral release of catecholamines from adrenergic tissues (12). After pretreatment with bretylium, the increases in amylase secretion and flow rate produced by sympathetic nerve stimulation were remarkably inhibited, but the increases in amylase secretion produced by noradrenaline, tyramine and nicotine were not.…”
Section: Sympathetic Denervationmentioning
confidence: 86%
“…But the question remains to be settled whether xylopinine releases serotonin in various tissues including the central nervous system or depresses the release of nor adrenaline from the adrenergic nerve terminal as bretylium (36).…”
Section: Discussionmentioning
confidence: 99%